CLOUD-BASED REPORT CARD ASSESSMENT APPLICATION AT INPRES BHOANAWA 1 ELEMENTARY SCHOOL - Sari, Patrisia Claudia; Tute, Kristianus Jago; Sala, Elvira Esperanza (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The rapid development of information technology has brought significant changes in the management of administrative processes in the field of education, including the process of student learning assessment. This study aims to design and develop a cloud-based report card application to assist Inpres Bhoanawa 1 Elementary School in managing academic data more effectively and securely. The system was developed using the PHP Native programming language and MySQL database, with a waterfall system development approach. The application has three main levels of access: school administrators, homeroom teachers, and subject teachers. School administrators are responsible for entering student data and granting access to homeroom teachers; homeroom teachers are responsible for entering learning objectives, student grades, and printing report cards; while subject teachers are responsible for entering formative and summative assessments as well as learning objectives. Cloud-based storage was chosen to ensure data security and availability, allowing access anytime and from any device connected to the internet. The test results show that the system functions properly according to the design, features a simple interface, and is easy to operate even by users with limited technological skills. The implementation of this system can speed up the report card creation process, reduce the risk of data loss, and minimize paper usage, making it more environmentally friendly. In conclusion, this cloud-based report card application serves as a practical solution for elementary schools in managing student assessments while improving the efficiency of educational administration. Keywords: report card application, cloud computing, PHP, MySQL